African literature, on what scale(s)? Comparing the recognition and relational resources of Sony Labou Tansi and Sylvain Bemba - (:unkn) unknown (My University, 2017)
Sony Labou Tansi (1947-1995) and Sylvain Bemba (1934-1995) are two authors – and friends – who were born and lived their whole lives in Congo-Brazzaville. Their literary works in French have been widely read and commented on in literary criticism in recent decades. But Sony Labou Tansi’s major international recognition is unmatched for Sylvain Bemba, a much more low-profile playwright and novelist. And yet, Bemba was considered ‘the true one-man-band of [national] cultural life ’ in the 1970s and the 1980s. As a journalist, he maintained exchanges within what he himself termed the ‘Congolese writer siblings ’ through prefaces, dedications, manuscripts’ proofreading, and book reviews. By a comparative study of the geographic scales of these two literary trajectories, this article explores the relationship between the literary recognition of authors from sub-Saharan Africa (located in a periphery dominated by the Parisian publishers) and their relational resources. Based on the renewal of research into ‘social networks’ in the sociology of literature, it questions the link between writers’ sociability (its form and geographic extension) and the production and reception of their works. The survey shows the importance of institutions located outside Africa in accessing the international literary stage. It also shows that a dense and closed local network that is favorable on a collective scale is less useful for an expanded literary reception than an open, heterogenous, and international network. This study also proposes a re-reading of the literary works of Labou Tansi and Bemba, through the obsession with human contact of the former, and the attraction of masks and erasure for the latter – visible in his contributions in the press.
Keywords: African Research